2018
DOI: 10.1021/acs.langmuir.7b03763
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry Dependence of Mechanochemical Reaction of Adsorbed Molecules—An Experimental Study on Tribopolymerization of α-Pinene on Metal, Metal Oxide, and Carbon Surfaces

Abstract: Mechanochemical reactions between adsorbate molecules sheared at tribological interfaces can induce association of adsorbed molecules, forming oligomeric and polymeric products often called tribopolymers). This study revealed the role or effect of surface chemistry of the solid substrate in mechanochemical polymerization reactions. As a model reactant, α-pinene was chosen because it was known to readily form tribopolymers at the sliding interface of stainless steel under vapor-phase lubrication conditions. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…[66] For the same molecule, the ∆𝑉𝑉 * also varies depending on the reactivity of the substrate on which the molecule is being sheared. [67] The reason for the differences or similarities between activation volumes may vary depending on the physical meaning of ∆𝑉𝑉 * itself. Reprinted with permission from Ref.…”
Section: B Interpretations Of the Magnitude Of Activation Volumementioning
confidence: 99%
“…[66] For the same molecule, the ∆𝑉𝑉 * also varies depending on the reactivity of the substrate on which the molecule is being sheared. [67] The reason for the differences or similarities between activation volumes may vary depending on the physical meaning of ∆𝑉𝑉 * itself. Reprinted with permission from Ref.…”
Section: B Interpretations Of the Magnitude Of Activation Volumementioning
confidence: 99%
“…[24][25][26] Intuitively, the molecules chemically anchored to the sliding surface would experience more mechanical shear than the molecules slipping within the interface. 27 However, the exact roles of surface chemistry and mechanical shear need to be unraveled for a deeper understanding of mechanochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of tripolymerization can be dated back to the 1950s [5][6][7], in which tribopolymer deposit was generated on metal contacts in the presence of hydrocarbons, while others discussed the mechanistic aspect of tribopolymerization and its application to improve tribological performance [8][9][10]. More recently, Kim et al [11][12][13] reported the use of vapor phase lubrication using alcohols and α-pinene that ultimately led to the formation of tribopolymers. Our group [14,15] described the use of cyclopropanecarboxylic acid (CPCa) as a model additive for tribopolymerization, which Qiang Ma and Arman Mohammad Khan have contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%